Ethnoveterinary medicinal plants and their utilization by the people of Soro District, Hadiya Zone, southern Ethiopia - Mulatu Hankiso; Zemede Asfaw; Bikila Warkineh; Abiy Abebe; Bihonegn Sisay; Asfaw Debella (BMC, 2024)
Abstract Background Ethnoveterinary studies are important to maintain the sustainability of livestock health and support people's livelihoods through the provision of food, maintaining livestock health, and other biological resources. This study was carried out in Soro District, southern Ethiopia, to identify, document and analyse plant species with ethnoveterinary uses along with the associated indigenous and local knowledge. Materials and methods Informants were selected using purposive (key informants) and systematic random sampling (general informants) methods. Data on ethnoveterinary plants and their uses were collected through semi-structured interviews, guided field walks, 13 focus group discussions with five to seven members in each and participant observation. Informant consensus factor and fidelity level were computed to identify the most common livestock ailment categories and the best plant species with ethnoveterinary use, respectively. Preference ranking methods were used to identify the potentially effective ethnoveterinary medicinal plants for the most frequently reported livestock ailments. The use diversity of multipurpose plants with ethnoveterinary importance was analysed using the analytical methods of ethnobotany including priority ranking, comparisons and important indices. The T-test statistic was used to compare knowledge differences among different social groups. Results A total of 132 plant species in 120 genera and 61 families were reported by informants as having ethnoveterinary uses. The plants are said to be used by the local communities in various ways to treat 50 livestock health problems. Higher number of informants (23.77%) cited Momordica foetida for the treatment of 16 livestock ailments. The highest informant consensus value for this species is associated with its use for treating blackleg in cattle; Nicotiana tabacum was cited for the treatment of 15 livestock ailments mainly recommended for the Lumpy Skin Disease/Ailment of bovines; Croton macrostachyus for treatment of 13 livestock ailments including wooden tongue, FMD in bovines; and Gymnanthemum amygdalinum for nine ailments mainly diarrhoea of all livestock types. Achyranthes aspera is claimed to provide the most effective treatment for Aspiration pneumonia (severe coughing in bovines, sheep and goats) alone, while Croton macrostachyus, Ximenia americana, Allium sativum and Juniperus procera were indicated as potential plant species to treat Lumpy Skin Disease in bovines in the order given. The fidelity level analysis showed that Datura stramonium, Dodonaea viscosa subsp. angustifolia and Asparagus africanus were potential medicinal plant species to treat the respective ailments of rabies, Peste des petits ruminants (PPR) and evil eye/spirit. Multipurpose plant species including Prunus africanus, Combretum molle and Afrocarpus falcatus have been highly threatened as indicated by direct matrix ranking mainly due to collection of fuel wood, construction materials and making household utensils, and farm implements rather than for other uses. Conclusion Soro District has rich and diversified livestock herbal medicinal resources, and indigenous knowledge of remedy preparations and applications is transmitted through generation lines. This resource faces anthropogenic threats with deforestation being the leading factor. Consequently, ethnoveterinary medicinal plants continue to decline before adequate and proper scientific documentation and testing are made. There is a dire need for planning and implementation of appropriate in situ and ex situ conservation strategies and to strive towards ensuring the survival and sustainable utilization of such important plant resources of Soro District. This must be supported by further documentation of the associated indigenous knowledge and pharmacological testing of the key promising species including Balanites aegyptiaca (novel species/NS to treat specific ailment), Brugmansia suaveolens (novel species/NS reported first to treat Livestock ailments/LsAs), Euclea divinorum (NS to treat specific ailments), Grevillea robusta (NS), Hagenia abyssinica (NS for the reported specific ailment), Pentanema confertiflorum (NS), Juniperus procera (NS), Maesa lanceolata (NS), Millettia ferruginea (NS for reported specific ailments), Schrebera alata/NS, Securidaca longepedunculata, Spiniluma oxyacantha/NS, Vepris nobilis (novel species reported first to treat LsAs), Zanthoxylum asiaticum /NS and Ximenia americana (NS for specific ailments). This ethnoveterinary study attempted to fill part of the gaps concerning the prevalent livestock health problems and the associated indigenous and local knowledge in the area.